Studi Tentang Pembuatan Lampion Berbahan Limbah Goni Rami Pada Mata Pelajaran Prakarya Siswa Kelas VIII SMP Negeri 2 Takengon T.A 2020/2021 - Pinte Ara; Azmi Azmi (Mahesa Research Center, 2021)
This study aims to determine how the ability of grade VIII students of SMP Negeri 2 Takengon in experimenting with jute sack waste as a material for making lantern handicrafts. This research uses descriptive qualitative research methods. The data collection techniques used were observation, interview and documentation. The population of this research is 180 students. The sample used consisted of five works using a sampling technique aimed at taking the subject not above average, random or regional, but based on a specific purpose. The assessment indicators examined in this study were color, unity and functional value. The results of the study on the manufacture of lanterns made from hemp sack waste in craft subjects for Class VIII students of SMP Negeri 2 Takengon in the academic year of 2020/2021 showed that overall they received a good score (B). This good value is seen from the work of students who use three assessment indicators in making lanterns made from jute sack waste and are assessed by three teams of assessors / validators.